Protease Activated Receptor 2 (PAR2) Induces Long-Term Depression in the Hippocampus through Transient Receptor Potential Vanilloid 4 (TRPV4) - Shavit-Stein, Efrat; Artan-Furman, Avital; Feingold, Ekaterina; Ben Shimon, Marina; Itzekson-Hayosh, Zeev; Chapman, Joab; Vlachos, Andreas; Maggio, Nicola (Frontiers in Molecular Neuroscience, 2017)
Protease Activated Receptors (PARs) are involved in regulating synaptic transmission and plasticity in the brain. While it is well accepted that PAR1 mediates Long Term Potentiation (LTP) of excitatory synaptic strength, the role of PAR2 in synaptic plasticity remains not well understood. In this study, we assessed the role of PAR2-signaling in plasticity at hippocampal Schaffer collateral-CA1 synapses. Using field potential recordings, we report that PAR2-activation leads to Long Term Depression (LTD) of synaptic transmission through a Protein Kinase A (PKA) -dependent, Transient Receptor Potential Vanilloid 4 (TRPV4) -mediated mechanism, which requires the activation of N-methyl-D-aspartate receptors (NMDAR). These results demonstrate that the effects of PAR2 on synaptic plasticity are distinct from what is observed upon PAR1-activation. Thus, we propose that the activation of different classes of PARs, i.e., PAR1 and PAR2, may set the threshold of synaptic plasticity in the hippocampal network by balancing LTP and LTD.